GAYA KEPEMIMPINAN DAN STRESS KERJA TERHADAP KINERJA KARYAWAN - Novika, Putri Wahyu (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
Human resources is one of the mean for the company to achieves its goal, for theyâre the one who market the product. However, in order to achieve its purposes, the company needs systematic and structured setting regulated in the form of organitation structure. Thus, it is hoped that every obstacle, like work pressure and leadership function, employees performance could work well.The sample in this research are 30, and the data is collected by spreading some quetionaire related to work pressure and leadership style and employees performance an Blitz Hotel Batam, where result of the analysis and discssion show that : (1) leadership styles has significant influence on employeed performance, (2) job work pressure hasnâtsignificant influence employeed performance.